Lightweight identity based online/offline signature scheme for wireless sensor networks - Alquraishee, Anser Ghazzaal Ali (2022)
Data security is one of the issues during data exchange between two sensor nodes in wireless sensor networks (WSN). While information flows across naturally exposed communication channels, cybercriminals may access sensitive information. Multiple traditional reliable encryption methods like RSA encryption-decryption and Diffie–Hellman key exchange face a crisis of computational resources due to limited storage, low computational ability, and insufficient power in lightweight WSNs. The complexity of these security mechanisms reduces the network lifespan, and an online/offline strategy is one way to overcome this problem. This study proposed an improved identity-based online/offline signature scheme using Elliptic Curve Cryptography (ECC) encryption. The lightweight calculations were conducted during the online phase, and in the offline phase, the encryption, point multiplication, and other heavy measures were pre-processed using powerful devices. The proposed scheme uniquely combined the Inverse Collusion Attack Algorithm (CAA) with lightweight ECC to generate secure identitybased signatures. The suggested scheme was analyzed for security and success probability under Random Oracle Model (ROM). The analysis concluded that the generated signatures were immune to even the worst Chosen Message Attack. The most important, resource-effective, and extensively used on-demand function was the verification of the signatures. The low-cost verification algorithm of the scheme saved a significant number of valued resources and increased the overall network’s lifespan. The results for encryption/decryption time, computation difficulty, and key generation time for various data sizes showed the proposed solution was ideal for lightweight devices as it accelerated data transmission speed and consumed the least resources. The hybrid method obtained an average of 66.77% less time consumption and up to 12% lower computational cost than previous schemes like the dynamic IDB-ECC two-factor authentication key exchange protocol, lightweight IBE scheme (IDB-Lite), and Korean certification-based signature standard using the ECC. The proposed scheme had a smaller key size and signature size of 160 bits. Overall, the energy consumption was also reduced to 0.53 mJ for 1312 bits of offline storage. The hybrid framework of identity-based signatures, online/offline phases, ECC, CAA, and low-cost algorithms enhances overall performance by having less complexity, time, and memory consumption. Thus, the proposed hybrid scheme is ideally suited for a lightweight WSN.